2018
DOI: 10.1063/1.5005979
|View full text |Cite
|
Sign up to set email alerts
|

Germanium diffusion with vapor-phase GeAs and oxygen co-incorporation in GaAs

Abstract: Vapor-phase germanium diffusion has been demonstrated in Zn-doped and semi-insulating GaAs in sealed ampoules with GeAs powders and excess arsenic. Secondary-ion-mass spectroscopy (SIMS) profiles indicate the presence of unintentional co-incorporation of oxygen in high densities (>1017/cm3) along with diffused germanium donors whose concentration (>>1018/cm3) determined by electro-chemical capacitance-voltage (ECV) profiler shows significant compensation near the surface. The source of oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…[28] Ge diffused in GaAs will tend to act as a donor in GaAs. [22,28] , where the Ge in-diffusion depth of up to hundreds of nanometers has been reported [7,26,29] and is dependent on annealing time and temperature. Surface modulation on nanoscale may be brought up on a Ge surface by annealing a thin Ge-layer on GaAs substrate.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[28] Ge diffused in GaAs will tend to act as a donor in GaAs. [22,28] , where the Ge in-diffusion depth of up to hundreds of nanometers has been reported [7,26,29] and is dependent on annealing time and temperature. Surface modulation on nanoscale may be brought up on a Ge surface by annealing a thin Ge-layer on GaAs substrate.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, use of other group IV elements involve some fundamental problems associated with large lattice mismatch (∼4% for silicon) and different thermal expansion coefficients. In-diffusion of Ge in GaAs [7,22,23] can results in GaAs 1-x Ge x structures [20,23] exhibiting direct band-gap with superior optical properties. [19] For semiconductors, bringing the structure down to nanoscale may fundamentally modify the properties of materials by inducing low-dimensional charge carrier confinement [24] and self-assembling, allowing the growth of well-defined random or aligned nano/quantum structures [24] without the need of sophisticated lithography techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the important factor of auto-diffusion of Si and Ge substrate materials on the grown III-V epitaxial structures are investigated to a lesser extent. Some of the work has reported that auto-diffused Si and Ge can occupy both the Ga and As sites in GaAs layers, grown by metal-organic vapor phase epitaxy (MOVPE) and molecular beam epitaxy (MBE), depending on the growth conditions (Dunlap Jr, 1954;Galiana et al, 2008;Wang et al, 2018;Gupta & Khokle, 1985). Also, by the increased amount of auto-diffusion of group IV elements into the III-V layer, the free carrier density starts reducing due to the charge carrier compensation.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work, it was reported that auto-diffused Ge into GaAs epilayer acts as an n-type dopant when grown at 860 C. The dopant density due to Ge diffusion at high temperature (860 C) in GaAs can be very high, >> 10 18 cm À3 . The thermal activation energy of the defect centers formed by the diffused Ge and the gallium vacancies (Ge Ga -V Ga ) are estimated from configurational coordination modeling (Wang et al, 2018). The auto-diffusion can be reduced by growing the barrier layer at low temperature, $ 475 C, with reduced time duration of growth (Galiana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%